2017
DOI: 10.1111/anae.14132
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and pharmacodynamics of sublingual sufentanil for postoperative pain management

Abstract: Achieving successful treatment of postoperative pain remains a challenge. Recently, a sufentanil sublingual tablet system has been developed for treatment of moderate-to-severe postoperative pain. The phenylpiperidine sufentanil is a potent analgesic that rapidly crosses the blood-brain barrier and selectively activates central μ-opioid receptors. The system makes use of a hand-held dispenser system, which contains forty 15-μg sufentanil sublingual micro-tablets. The patient can release one tablet at 20-min in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 25 publications
(42 reference statements)
3
23
0
3
Order By: Relevance
“…Lipophilic, nonionized drug molecules have rapid uptake from sublingual tissues into the plasma as well as rapid uptake from the plasma to the l-opioid effector site in the central nervous system. It is mainly metabolized in the liver and enterocytes of the small intestines [26].…”
Section: Fig 4 Patient Satisfactionmentioning
confidence: 99%
“…Lipophilic, nonionized drug molecules have rapid uptake from sublingual tissues into the plasma as well as rapid uptake from the plasma to the l-opioid effector site in the central nervous system. It is mainly metabolized in the liver and enterocytes of the small intestines [26].…”
Section: Fig 4 Patient Satisfactionmentioning
confidence: 99%
“… 1 6 The SSTS system is developed by AcelRx Pharmaceuticals (Redwood City, CA, USA) and is marketed in Europe as Zalviso™ by Grünenthal GmbH (Aachen, Germany). 5 The noninvasive hand-held SSTS is in fact a patient-controlled analgesia (PCA) device without the need for an intravenous (IV) catheter. The SSTS device holds a cartridge with 40 microtablets, each of which contains 15 μg sufentanil.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that dexmedetomidine has good analgesic sedative effect, and also significantly reduces the dose of anesthetic drugs required, reduces the duration of coma and shorten duration of mechanical ventilation ( 6 ). Sufentanil is an effective analgesic that rapidly crosses the blood-brain barrier and selectively activates central µ-opioid receptors ( 7 ), with a very high therapeutic index in clinical studies. There is no active metabolite, but there is a high degree of lipophilic property ( 8 ).…”
Section: Introductionmentioning
confidence: 99%